EFEKTIFITAS HUBUNGAN PASAL 289 KUHP DENGAN PACARAN DI ERA MILENIAL (Jurnal Magister Hukum Perspektif, 2022)
The purpose of this paper is to analyze the effectiveness of the relationship between Article 289 of the Criminal Code and dating in the millennial era. This research uses a statutory approach and a conceptual approach. The results showed that the ineffectiveness of article 289 of the Criminal Code with dating in the millennial era. This is because times are changing, changes in the concept of courtship are also shaped by the mindset of most teenagers who do not want to be considered a child but will be more proud if they are considered an adult. So there is also a view that sexual behavior is considered a symbol of maturity status. There is still a perspective among law enforcement officials that sexual violence occurs because of willingness (mutual consent). The victim's condition is also exacerbated by patriarchal views that often see women as the cause or trigger of sexual violence. Keywords: 289 KUHP, Millennial Era Dating